The estate [videorecording (DVD)] - Craig, Dean, 1974-; Collette, Toni; Faris, Anna, 1976-; Duchovny, David; DeWitt, Rosemarie; Livingston, Ron; Mejia, Keyla Monterroso; Turner, Kathleen, 1954- (Universal, 2023)
Two sisters attempt to win over their terminally ill, difficult-to-please aunt in hopes of becoming the beneficiaries of her wealthy estate, only to find the rest of their greedy family members have the same idea in this hilarious comedy about family being the worst.